Paediatric nursing research in Australia: A descriptive survey. Issue 1 (February 2020) - Ullman, Amanda J; Xu, Hui; Mitchell, Amy; Doyle, Rebecca; Kleidon, Tricia; Rickard, Claire; Cooke, Marie; Harley, Amanda; Kain, Victoria; Forster, Elizabeth; Petsky, Helen
Abstract: Background: High-quality paediatric nursing research is needed to inform and advance nursing practice. To date there has not been a systematic description of the current state of Australian paediatric nursing research. Aim: The aim of this study was to identify and describe demographic, professional, and research characteristics of Australian nurses currently active in paediatric nursing research. Methods: An Australia-wide cross-sectional online survey was used. Research-active paediatric nursing academics/clinicians completed items relating to demographic characteristics, professional qualifications/roles, clinical/research experience, research focus, role/s within the research team, research output, grant funding, and dissemination strategies. Findings: Of the 100 survey respondents, there was an average 26.7 years nursing experience, but only 9.4 years research experience. Most were employed in tertiary acute care facilities (40.0%) or universities (37.0%), with backgrounds in intensive/critical care (45.2%), medical/surgical nursing (23.7%) or primary care/community health (22.6%). Most held higher research degree/s (89.9%) and worked within interdisciplinary teams (89.0%) across the spectrum of research activities. Research outputs were: median 20 career-total publications (h-index = 9.5, citations = 200), and an average 5 grants awarded (median AUD21, 000 total funding). Discussion: Paediatric nursing researchers in Australia have diverse educational and professional backgrounds, research foci, and work locations. Although research output indices place respondents on par with researchers from other health disciplines relative to career stage, total research funding and national funding success is notably lower compared to researchers from other health disciplines. Conclusion: Paediatric nursing research involves diverse roles, skills, experience and clinical foci. This study represents a first step toward developing a programmatic approach to paediatric nursing research in Australia.